Multiplication végétative de Dacryodes edulis (G. Don) H.J. Lam. par marcottage aérien - Elomo, Christiane; Nguénayé, Blandine; Tchoundjeu, Zacharie; Assah, Ebenezar; Tsobeng, Alain; Avana, Marie-Louise; Bell, Martin J.; Nkeumoe, Frederik (Afrika Focus, 2014)
Dacryodes edulis (G. Don) H. J. Lam. (Burseraceae) is a high-value fruit tree in West and Central Africa. Air layering of this species is now under control, but uncertainty remains as to the effect of a number of factors on rooting; these include cloning the type of propagule, the orientation of branches and the position of the marcots in the crown. A series of experiments were conducted to evaluate the effect of cloning, the type of propagule (cuttings and marcots), position in the crown (lower and upper) and the orientation of branches (plagiotropic, oblic and orthotropic) on the tree ́s rooting ability. For the frst three factors, older clones of 10 years with a normal maturation were bedded in equal proportions of decomposed sawdust and arable soil. To test the orientation factor late maturing trees of over 20 years bedded in, decomposed sawdust were used. Ten months after the setting up of marcots, the results showed that the clonal effect significantly (p<0.001) af- fects the rooting of marcots. The best result was obtained for clones MA/DE/40M, BUM/DE/36M and DE/M/2-70C. The type of propagule had a significant effect (p<0.012) on percentage of rooting marcots. On the dead marcots, this effect was significant (p<0.038) from the eighth month. No significant effect (p = 0.124) of the position of the branch in the crown was recorded on the rooting of marcots. However, the upper crown had apparently a high percentage of rooting (39.59 ± 3.37%) compared to that of the lower crown (31.94 ± 3.44%) at 10 months. The percentage of dead marcots recorded was high at lower crown marcots (40.28 ± 4.08%) and the mean number of primary roots was low (6.97 ± 0.87 %) compared to the upper part (33.33 ± 3.91 and 7.36 ± 0.8% respectively). Nine months after the setting up of marcots, the orthotropic branches showed a high number of primary roots (13.55 ± 1.22%) and a low percentage of dead marcots (6.67 ± 4.55%) compared to plagiotropic branches (7.84 ± 0.77 and 26.67 ± 8.05% respectively). With respect to the orientation of branches, no significant (p = 0.45) effect on the rooting of marcots was recorded, but the rooting percentage of marcots on plagiotropic and oblic branches (43.33 ± 9.05%) was high compared to the percentage of orthotropic branch (30 ± 8.34%). It can therefore be concluded from this study that orthotropic branches of D. edulis, upper crown are among the best parameters for air layering. Key words: domestication, African plum tree, clone, marcots, Cameroon